Measuring discourse coherence in anomic aphasia using Rhetorical Structure Theory. (4th July 2018) - Kong, Anthony Pak-Hin; Linnik, Anastasia; Law, Sam-Po; Shum, Waisa Wai-Man
Abstract: Purpose : The existing body of work regarding discourse coherence in aphasia has provided mixed results, leaving the question of coherence being impaired or intact as a result of brain injury unanswered. In this study, discourse coherence in non-brain-damaged (NBD) speakers and speakers with anomic aphasia was investigated quantitatively and qualitatively. Method : Fifteen native speakers of Cantonese with anomic aphasia and 15 NBD participants produced 60 language samples. Elicitation tasks included story-telling induced by a picture series and a procedural description. The samples were annotated for discourse structure in the framework of Rhetorical Structure Theory (RST) in order to analyse a number of structural parameters. After that 20 naïve listeners rated coherence of each sample. Result : Disordered discourse was rated as significantly less coherent. The NBD group demonstrated a higher production fluency than the participants with aphasia and used a richer set of semantic relations to create discourse, particularly in the description of settings, expression of causality, and extent of elaboration. People with aphasia also tended to omit essential information content. Conclusion : Reduced essential information content, lower degree of elaboration, and a larger amount of structural disruptions may have contributed to the reduced overall discourse coherence in speakers with anomic aphasia.